Kajian Persepsi Komuter Terhadap Mobilitas Cerdas Pada BRT Transjakarta Koridor 13 selama Pandemi COVID-19 - Muhamad Devandra Adiwinata; Yudi Basuki (Jurusan Perencanaan Wilayah dan Kota, 2023)
Jabodetabek with DKI Jakarta as its centre, is a rapidly growing area. Therefore, the DKI Jakarta Provincial government continues to strive to create a Smart City to deal with problems and encourage sustainable city development. One of the concepts in a Smart City is Smart Mobility. Jabodetabek has more than 3 million residents who are commuters. The Transjakarta Bus Rapid Transit (BRT) is a government's effort to realize smart mobility in DKI Jakarta and support movement through the management and technological innovation in public transportation for citizens. The COVID-19 pandemic has caused a drastic decline in the number of public transportation users in the last two years, including BRT Transjakarta. This study aimed to identify aspects of Smart Mobility on BRT Transjakarta Corridor 13 and examine the characteristics and perceptions of commuters towards Smart Mobility of the Transjakarta BRT Corridor 13 during the COVID-19 pandemic. The research resulted in observations from the operations and facilities on the Transjakarta BRT Corridor 13, which were grouped based on the five aspects of Smart Mobility: integration, accessibility, security, flexibility, and efficiency. Socio-economic characteristics and types of movement indicate that these services are used mainly by the productive age group to work, as well as departing from bus stops in Tangerang City with a round-trip type of use. The ease-of-use perception of the five aspects of intelligent mobility resulted in a positive response of 87.2%. Similar results were obtained from the perceived usefulness towards smart mobility aspects of Corridor 13, which resulted in a positive response of 86.6%. Perceived ease-of-use and perceived usefulness of BRT Transjakarta Corridor 13 both resulted in positive response that BRT Transjakarta Corridor 13 if examined from the five aspects of smart mobility (integration, accessibility, security, flexibility, and efficiency) apart from being easy to use, is also beneficial for users who use BRT Transjakarta Corridor 13.